2020
DOI: 10.1038/s41368-020-00103-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological efficacy of perpendicular type-I collagen protruded from TiO2-nanotubes

Abstract: The aim of this study was to evaluate the biological efficacy of a unique perpendicular protrusion of type-I collagen (Col-I) from TiO2 nanotubes (NT-EPF surface). We hypothesized that the NT-EPF surface would play bifunctional roles in stimulating platelet-mediated fibroblast recruitment and anchoring fibroblast-derived Col-I to form a perpendicular collagen assembly, mimicking the connective tissue attachment around natural teeth for the long-term maintenance of dental implants. Ti surface modification was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…There have been many trials to increase fibroblast attachment to titanium surfaces by using bioactive protein coatings such as fibroblast growth factor-2 [119], laminin [120], fibronectin [121,122], and collagen type-1 [123]. These techniques successfully increase fibroblast attachment, but the use of growth factors or cytokines should be well managed to maintain their activity, while coating techniques suffer from the propensity of detachment at the interface between the base material and coating.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many trials to increase fibroblast attachment to titanium surfaces by using bioactive protein coatings such as fibroblast growth factor-2 [119], laminin [120], fibronectin [121,122], and collagen type-1 [123]. These techniques successfully increase fibroblast attachment, but the use of growth factors or cytokines should be well managed to maintain their activity, while coating techniques suffer from the propensity of detachment at the interface between the base material and coating.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was concluded that electrophoretic fusion of type-I collagen in nanotube titanium can be used to fabricate more robust soft tissue seals. [169]. Electrophoretic deposition has several advantages and disadvantages, which are mentioned in the Table 9.…”
Section: Advantages/disadvantages Referencesmentioning
confidence: 99%
“…The surface was created through an electrochemical anodization process using a titanium piece (anode) and a copper piece (cathode). 17,22,23 This way, the negatively charged C-terminus of collagen fibers could be attached perpendicularly to the positively charged TNT surface. These collagen fibers, aligned in an ideal manner, not only demonstrated strong binding resistance against sonification forces, but also inhibited formation of epithelial sheets, suggesting the potential for preventing epithelial downgrowth between the collagen fibers and the titanium surface.…”
Section: Introductionmentioning
confidence: 99%